Complete Controllability of Fractional Neutral Differential Systems in Abstract Space - Fang Wang; Zhen-hai Liu; Jing Li (Abstract and Applied Analysis)
By using fractional power of operators and Sadovskii fixed point theorem, we study the complete controllability of fractional neutral differential systems in abstract space without involving the compactness of characteristic solution operators introduced by us.